Diversidade e funcionalidade de fungos endofíticos na remediação do mercúrio - Souza, William Pietro de (2017)
The mercury is a heavy metal that when incorrect used in gold processing, represents an important source of environmental contamination, with bioaccumulation risk. In this perspective, remediation strategies involving the use of biological systems such as microorganisms are considered ideal. Thus, our objective is to determine the mercury contamination effect in the community of endophytic fungi and to investigate the biotechnological potential of endophytic fungi in the bioremediation of soils contaminated with mercury. The endophytic fungi isolation of Aeschynomene fluminensis (A) and Polygonum acuminatum (P) roots at sites with (+ Hg) and without (- Hg) mercury in Pantanal-MT occurred by dependent and independent methods of culture. A strain of each isolated species was submitted to mercury tolerance tests, through the mycelium growth in BDA medium supplemented with 30 μg.mL-1 of Hg+2. In the control there was not addition of Hg+ 2. The strains were daily evaluated and based on the mycelium diameter, the growth rate (μ) and the Tolerance Index (TI) were calculated. The strains with IT ≥ 0.9 were selected to determine the maximum concentration of mercury that inhibits mycelial growth (MIC) and the in vitro bioremediation capacity of Hg+2. The cultivable endophytic fungi community was represented by 190 strains and based on the ITS region, the isolated strains were distributed in 70 species. For the independent culture analysis, we obtained 6.228.702 fungal sequences of high quality from the LSU region with Illumina Miseq, whose sequences were distributed in 419 OTUS. Both analyzes showed that mercury structures endophytic fungi communities. In relation to the tolerance of cultivable strains to mercury, 32 lines (45.7%) had IT higher than 0.9, and in most of these resistant strains (84.7%) the MIC was above 600 μg mL -1 of Hg+2. By the capacity of in vitro bioremediation and tolerance to Hg+2, the C. geniculata P1, Lindgomycetaceae P87, Aspergillus sp. A31 and Westerdykella sp. P71 strains were selected for bioremediation, in vitro bioaccumulation and A. fluminensis and Z. mays growth promotion in soil with and without the addition of Hg+2. About 86 to 100% of the mercury was removed from the culture medium by these strains. The inoculated plants accumulated higher dry biomass and the Hg+2 bioaccumulation in plant tissues was favored by inoculation. The concentrations of Hg+2 soil residual was reduced in the inoculated plants. In face of the data, it is clear that mercury promotes changes in the composition of endophytic fungi communities and that A. fluminensis and Z. mays inoculation with resistant endophytic fungi strains to mercury improves host growth and mercury phytoextraction. Therefore, the strains are promising to improve the Hg+2 phytoremediation, representing an ecologically viable alternative for environments decontamination, especially wetlands contaminated areas with high concentrations of Hg+2.